TINJAUAN SOSIO YURIDIS TERHADAP KECELAKAAN LALU LINTAS DI KABUPATEN BUTON - Mustafa, La Ode Ali; Marzuki, Marzuki (Jurnal Ilmu Hukum Kanturuna Wolio, 2024)
This research aims to find out the causes of traffic accidents in the Buton Police Area and to find out the form of handling strategies used by the Government and law enforcement in solving the problem of traffic accidents in the Buton Police Area. The method used in this research is empirical legal research with data collection through document studies, interviews, and questionnaires for respondents. Sampling was done non-randomly with purposive sampling technique. Data was analysed using qualitative analysis The results showed that the causes of traffic accidents in the Buton Police Legal Area. In general, there are three main factors that cause accidents; driver factors, vehicle factors, road environment factors. Accidents that occur in general are not only caused by one factor, but the result of interaction between other factors. The form of handling carried out involves the government in this case is the Buton Regency Transportation Office and the Law Enforcement in this case is the Buton Police Traffic Unit.